The jet/wind outflow in Centaurus A: a local laboratory for AGN feedback. Issue 3 (9th November 2017) - McKinley, B; Tingay, S J; Carretti, E; Ellis, S; Bland-Hawthorn, J; Morganti, R; Line, J; McDonald, M; Veilleux, S; Wahl Olsen, R; Sidonio, M; Ekers, R; et al.
Abstract: We present new radio and optical images of the nearest radio galaxy Centaurus A and its host galaxy NGC 5128. We focus our investigation on the northern transition region, where energy is transported from the ∼5 kpc (∼5 arcmin) scales of the northern inner lobe (NIL) to the ∼30 kpc (∼30 arcmin) scales of the northern middle lobe (NML). Our Murchison Widefield Array observations at 154 MHz and our Parkes radio telescope observations at 2.3 GHz show diffuse radio emission connecting the NIL to the NML, in agreement with previous Australia Telescope Compact Array observations at 1.4 GHz. Comparison of these radio data with our wide-field optical emission-line images show the relationship between the NML radio emission and the ionized filaments that extend north from the NIL, and reveal a new ionized filament to the east, possibly associated with a galactic wind. Our deep optical images show clear evidence for a bipolar outflow from the central galaxy extending to intermediate scales, despite the non-detection of a southern radio counterpart to the NML. Thus, our observational overview of Centaurus A reveals a number of features proposed to be associated with active galactic nucleus feedback mechanisms, often cited as likely to have significant effects in galaxy evolution models. As one of the closest galaxies to us, Centaurus A therefore provides a unique laboratory to examine feedback mechanisms in detail.